The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1370/afm.982
|View full text |Cite
|
Sign up to set email alerts
|

Managing Chronic Disease in Ontario Primary Care: The Impact of Organizational Factors

Abstract: PURPOSE New approaches to chronic disease management emphasize the need to improve the delivery of primary care services to meet the needs of chronically ill patients. This study (1) assessed whether chronic disease management differed among 4 models of primary health care delivery and (2) identifi ed which practice organizational factors were independently associated with high-quality care. METHODSWe undertook a cross-sectional survey with nested qualitative case studies (2 practices per model) in 137 randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
144
1
10

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(159 citation statements)
references
References 34 publications
4
144
1
10
Order By: Relevance
“…In Canada, high quality chronic disease management was found to be associated with the presence of a nurse practitioner (Russell et al, 2009), and an evaluation of nurse-led shared care in the Netherlands (Irmgard et al, 2002), where generalists and specialists work together with the focus on the patients needs, suggested that many participants preferred the treatment by the nurse practitioner in the GPs office to traditional care by the medical specialist at the outpatient clinic. However, patients felt it was important to maintain a direct link with the medical specialist, and the nurse practitioner model had limitations such as the requirement for the nurse to contact the medical specialist in case of a complication as this was felt to be too time consuming.…”
mentioning
confidence: 99%
“…In Canada, high quality chronic disease management was found to be associated with the presence of a nurse practitioner (Russell et al, 2009), and an evaluation of nurse-led shared care in the Netherlands (Irmgard et al, 2002), where generalists and specialists work together with the focus on the patients needs, suggested that many participants preferred the treatment by the nurse practitioner in the GPs office to traditional care by the medical specialist at the outpatient clinic. However, patients felt it was important to maintain a direct link with the medical specialist, and the nurse practitioner model had limitations such as the requirement for the nurse to contact the medical specialist in case of a complication as this was felt to be too time consuming.…”
mentioning
confidence: 99%
“…Other studies investigating relationships between diabetes/ chronic disease care and practice characteristics (including EHR, 33 Medicaid percentage, 34 community health centers, [35][36][37] and practice size 38,39 ) have reported mixed results. Interestingly, we find that rural and smaller practices, which often do not have as many connections to resources as urban practices, showed significantly greater improvement in both the CQI-and RAP-facilitated arms, while urban practices, usually with more available resources, saw more improvement in the self-directed arm.…”
Section: Discussionmentioning
confidence: 99%
“…Des études canadiennes récentes ont montré que les modèles de soins primaires qui incluent des infirmières praticiennes amélioraient la gestion des maladies chroniques (Russell et al, 2009) et l'accessibilité, en particulier dans les zones peu desservies (Centre for Rural and Northern Health Research, 2006;Martin-Misener et al, 2009). La satisfaction des patients pour ce rôle continue à être élevée (Thrasher et al, 2008).…”
Section: Evaluationsunclassified
“…Au Canada, les résultats d'une étude de 2009 évaluant la gestion d'un ensemble de maladies chroniques dans les soins primaires ont établi que la qualité des soins (en termes de mesures de processus) était supérieure dans les centres de santé « communautaires » qui impliquaient au moins une infirmière praticienne et où tout personnel était salarié (Russell et al, 2009). Parmi les différents types de modèles de soins primaires, une plus grande qualité de prestations de soins de maladies chroniques était plus probable lorsqu'une infirmière praticienne intervenait.…”
unclassified
See 1 more Smart Citation